Peran Kearifan Lokal Etnis Padang Pariaman dalam Mendukung Pembangunan Kabupaten Banyumas - Mukhyidin, Azmy Habib; Sugiarti, Lina; Pamuji, Toni Dwi; Huwaida, Salma Ulya; Yuliyana, Rita (Da'wa Faculty UIN Saizu Purwokerto, 2026)
This study aims to analyze the role of the local wisdom of the Padang Pariaman ethnic community in supporting the development of Banyumas Regency through social, economic, cultural, and institutional dimensions. A qualitative approach was employed using data collected through in-depth interviews with the Chairman of the Padang Pariaman Family Association (PKDP) Banyumas, participant observation of community activities, and review of regional policy documents and academic literature. The findings reveal that the local wisdom of the Padang Pariaman community—including katok ampe, raso pareso, a strong work ethic, kinship-based networks, and the adaptive principle of “where the earth is trodden, there the sky is upheld”—functions as cultural capital that strengthens social integration between migrants and the local Banyumas community. Economically, microenterprises and the culinary sector managed by Padang Pariaman migrants contribute significantly to job creation, income generation, and regional revenue. Socially, solidarity through the PKDP association is manifested in community-based activities such as fundraising, humanitarian support, and women’s empowerment initiatives. Culturally, the preservation of Minangkabau traditions in the public sphere enriches cultural diversity and supports the development of an inclusive regional identity. These findings indicate that the local wisdom of the Padang Pariaman diaspora serves not only as an ethnic marker but also as sustainable development capital that positively contributes to strengthening the creative economy, social cohesion, and multicultural character of Banyumas Regency.